Prevalence of Undernutrition and its Socio-Demographic Determinants among Rural Bengalee Muslim Preschool Children of Bankura District, West Bengal, India - Hoque, Sk Anamul; MD Anisujjaman; Bose, Kaushik; Biswas, Sadaruddin (Anthropological Review, 2025)
Despite recent global economic growth, the high prevalence of child undernutrition is an urgent public health issue in low and middle-income countries, including India. Moreover, one-third of infant mortality is associated with undernutrition. The present cross-sectional study aims to report the burden of undernutrition and to explore its association with socio-demographic variables among the Bengalee Muslim preschool children of Bankura district, West Bengal, India. This present study was conducted among 800 preschool children (400 males and 400 females) aged 12 to 59 months. The children were selected using a systematic random sampling method, and the sample size was estimated using standard formula. Descriptive, parametric, non-parametric, and inferential statistical analyses were performed accordingly. Males were taller and heavier than females. Significant age variations in mean height and weight were found among the study participants. The overall prevalence of stunting, wasting, and underweight was 23.0%, 30.5%, and 36.0%, respectively. The results of the chi-square test showed that all the socio-demographic variables were significantly associated with the nutritional status of these children. A multivariate logistic regression revealed that non-exclusive breastfeeding, higher birth order, and the lower mothers’ age at childbirth were the significant predictors of stunting. Low family income, large family size, and low maternal educational status were the significant predictors of wasting. Moreover, low family income, non-exclusive breastfeeding, and mothers’ age at childbirth were significant predictors of underweight. The findings of the present study revealed that there were numerous determinants of undernutrition among the Bengalee Muslim preschool children. Therefore, the appropriate government and non-government agencies should adopt the policy for an income-generating scheme to enhance household income, awareness of exclusive breastfeeding, family planning, adult education programmes, and surveillance against child marriage.